2018
DOI: 10.1039/c8tc03091j
|View full text |Cite
|
Sign up to set email alerts
|

Towards the application of Al2O3/ZnO nanolaminates in immunosensors: total internal reflection spectroscopic ellipsometry based evaluation of BSA immobilization

Abstract: Signal enhancement due to multiple reflections in a total internal reflection configuration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…We found that the following layer stack gave satisfactory fit for thickness determination: (i) aluminum substrate had n, k values by Rakić et al [59]; (ii) a fixed 40 nm thickness barrier layer was described by effective values from Bruggeman model [60] with 20% Al and 80% Al 2 O 3 [61]; (iii) for porous PAAO/ZnO/void layer with thickness to be determined by fitting, a fixed effective value n = 1.6 was used; (iv) and, finally, for the 35 nm ZnO layer we used a refractive index value of 1.95 [42]. Typical fitted reflectance spectra along with measured data are shown in Figure 3a,b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the following layer stack gave satisfactory fit for thickness determination: (i) aluminum substrate had n, k values by Rakić et al [59]; (ii) a fixed 40 nm thickness barrier layer was described by effective values from Bruggeman model [60] with 20% Al and 80% Al 2 O 3 [61]; (iii) for porous PAAO/ZnO/void layer with thickness to be determined by fitting, a fixed effective value n = 1.6 was used; (iv) and, finally, for the 35 nm ZnO layer we used a refractive index value of 1.95 [42]. Typical fitted reflectance spectra along with measured data are shown in Figure 3a,b.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, ZnO nanostructures have been proposed for biosensing using different readout schemes, including photocurrent measurements [39][40][41], combination of ellipsometry and the surface plasmon resonance [42], UV photoluminescence [43], and others. Different physical mechanisms of molecule interaction with ZnO for biosensing have been described, for example, charge transfer, and hydrophobic and electrostatic interaction between the biomolecule and ZnO surface [44].…”
Section: Introductionmentioning
confidence: 99%
“…Optical ellipsometry-based techniques have great potential to be applied in the design of various immunosensors [ 120 ]. Comparing with other existing methods (ELISA, RT-PCR, indirect fluorescent, western blot) of SARS-CoV detection, the imaging ellipsometry-based approach has established itself as a direct, nondestructive, quick, label-free, simple, and low-cost technique [ 121 ].…”
Section: Affinity Biosensors For Covid-19 Diagnosismentioning
confidence: 99%
“…It was shown that higher sensitivity of this method in case of multilayered ZnO structures have been achieved because of multiple reflections of the light occurring in a total internal reflection mode. Especially it was noticeable for ellipsometric parameter Δ, which under total internal reflection condition depends on the angle of incidence [23,24,25].…”
Section: Introductionmentioning
confidence: 99%